2019
DOI: 10.3186/jjphytopath.85.25
|View full text |Cite
|
Sign up to set email alerts
|

Fruitlet core rot of pineapple (<i>Ananas comosus</i>) caused by <i>Fusarium ananatum</i> in Japan

Abstract: Fruitlet core rot of pineapple (Ananas comosus) has been found in Okinawa Prefecture, Japan since a few decades ago. A fungus frequently isolated from the diseased fruits was identified as Fusarium ananatum based on morphological and cultural characteristics and molecular analyses of EF-1α,β-tubulin and histone H3 DNA sequences. The isolates reproduced the symptoms on pineapple fruits after inoculation using toothpicks and were reisolated from the inoculated symptomatic fruits. This is the first report of frui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…In the cross, 'Yugafu' was used as a cross-parent with good fruit-eating quality, large fruit size, and high adaptability for the Okinawa climate. 'Yonekura' was used as a possible source of long shelf life, fruitlet core rot tolerance (Yamashiro et al 2019), and yellow flesh color. These cross-seedlings were planted in a pineapple selection field at OPARC-Nago at a density of 40,000 plants/ha, which is the normal planting density for commercial pineapple production in Okinawa.…”
Section: Methodsmentioning
confidence: 99%
“…In the cross, 'Yugafu' was used as a cross-parent with good fruit-eating quality, large fruit size, and high adaptability for the Okinawa climate. 'Yonekura' was used as a possible source of long shelf life, fruitlet core rot tolerance (Yamashiro et al 2019), and yellow flesh color. These cross-seedlings were planted in a pineapple selection field at OPARC-Nago at a density of 40,000 plants/ha, which is the normal planting density for commercial pineapple production in Okinawa.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies in several regions have shown that FCR is caused by various fungal pathogens. For example, Talaromyces amestolkiae and Talaromyces stollii were found to cause FCR in Japan and Reunion Island (Vignassa et al 2021;Yamashiro et al 2019); Fusarium oxysporum, Fusarium proliferatum, and Fusarium sacchari were demonstrated to cause FCR in Reunion Island (Vignassa et al 2021); and Fusarium ananatum was identi ed as an FCR pathogen in China, Japan, Reunion Island, and South Africa (Gu et al 2015;Jacobs et al 2010;Vignassa et al 2021;Yamashiro et al 2019). Several other species in the genera Aspergillus, Clonostachys, Curvularia, Diaporthe, Epicoccum, Fusarium, Pestalotiopsis, Penicillium, Rhizopus, and Trichoderma have also been found in diseased fruitlets (Vignassa et al 2021).…”
Section: )mentioning
confidence: 99%